The transition region above sunspots - Hui Tian; Tanmoy Samanta; Jingwen Zhang (Geoscience Letters, 2018)
Abstract Over decades, sunspots and their fine structures have been studied in detail at the photospheric level with different ground-based telescopes, as the surface of the Sun primarily emits light in the visible wavelengths. For a very long period, the upper atmosphere above the sunspot regions, especially the transition region (TR) above sunspots where the plasma emits light in the far ultraviolet (FUV) and extreme ultraviolet (EUV), has been poorly understood. In the past decades after the development of space instrumentations, FUV and EUV observations have uncovered many secrets of the TR above sunspots. In this paper, we present a brief review of research results about the TR structures and dynamics obtained through imaging and spectroscopic observations of sunspots in the past ~ 20 years. Though these observations have gathered remarkable and detailed information and greatly improved our understanding of the TR above the sunspots, paradoxically, they leave us with many new questions which should be answered in the future.